Rozner, Sarah (audio interview #9 of 20) - Rozner, Sarah (b. 1892 - d. 12/?/1980); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the seventeenth interview with Sarah Rozner conducted in her home. The interview is rather wide ranging and covers both her protective attitude about women in the union and her philosophical and political beliefs. TOPICS - development of women's and feminist consciousness; activism on behalf of women; personal struggles in the union; and attitude towards women forming their own labor union;attitude towards a separate women's union; ideas about progress, social evolution and capitalism versus industrialism; and feelings of failure with regard to the Women's Local in Chicago; 11/29/1973